USAHATANI PEPAYA CALIFORNIA: ANALISIS KELAYAKAN FINANASIAL SUATU STUDI KASUS DI DESA BENDANG RAYA KECAMATAN TENGGARONG KABUPATEN KUTAI KERTANEGARA - Ida Bagus Made Agung Dwijatenaya; Agung Enggal Nugroho; Ahmad Iskandar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The aims of this experiment was to determine the effect of the application of Agrib Compost liquid organic fertilizer to the growth of bud grafting seedling of Lai (Durio kutejensis HASSK. BECC) var. Mahakam. The experiment used a Randominzed Block Design (RCBD) with Agrib Compost liquid organic fertilizer treatment (P) 8 level and 3 tests made up of p0 = without treatment (control), p1 = (2 ml L-1 water), p2 = (4 ml L-1 water), p3 = (6 ml L-1 water), p4 = (8 ml L-1 water), p5 = (10 ml L-1 water), p6 = (12 ml L-1 water), p7 = (14 ml L-1 water). The result of the experiment indicated that the treatment of Agrib Compost liquid organic fertilizer, it had a very significant effect to the age of broken buds but had no significant effect to the length of bud parameters, the number of leaves and the diameter of the stem. The treatment of Agrib Compost liquid organic fertilizer 14 ml L-1 water, providing better growth in age parameters of broken buds, bud length, and the number of leaves.